A taxonomic approach on diagnostic characters used to define new pterosaur taxa and an estimation of pterosaur diversity - Fernandes, Denis Luiz; Nunes, Ivan [UNESP]; Costa, Fabiana Rodrigues (FapUNIFESP (SciELO), 2021)
Diagnostic characters from 227 pterosaur species were listed, separated into cranial or post-cranial elements and counted. From 21 post-cranial and 23 cranial elements, most diagnostic characters were related to phalanges (15%) and rostrum. Post-cranial characters comprise 44.23%, and cranial characters 55.77% of all characters used in pterosaur diagnoses. The highest correlation between diagnostic features occurs between the coracoid and the scapula. 25.11% and 28.63% of sampled taxa were diagnosed with 3-4 and 5-6 characters, respectively. The mean number of 6.79 characters was found in specimens with both cranial and post-cranial elements, and 4.86 and 4.17 in those with just cranial or post-cranial elements, respectively. 31 from 227 species (13.7%) were erected based on single elements, which are most frequently complete or partial mandibles (n=18). We estimate that 23.4% of the total pterosaur genera are currently known, with 90% of this diversity to be unveiled up to 2145. As the requirements of broad and cautious revision of genus/group must be undertaken, and some deposits will provide mostly fragmented and incomplete material, the assignment of fairly incomplete specimens to the most inclusive taxonomic level is feasible. Tracing this scenario can guide future works on the description of new pterosaur taxa.
Keywords: Morphology-based species; Pterosauria; Systematic Biology; Taxonomy